2006
DOI: 10.1063/1.2162266
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation studies in organic-inorganic nanoclusters

Abstract: Inorganic/organic nanocomposites of iron oxide and polypyrrole, prepared by two different techniques, namely, simultaneous gelation/polymerization and polymerization over core iron oxide particles, were investigated for their structural and magnetic properties. The presence of the polymer was confirmed by Fourier transform infrared spectroscopy. The magnetic properties were found to be very sensitive not only to the concentration of polymer but also to the method of preparation. ac susceptibility measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, several other studies have reported on the effect of aggregation on AC susceptibility of magnetic nanoparticle suspensions [28,40,41], although most look at shifts in the peak of frequency response or changes in blocking temperature. However, theoretical predictions do show that imaginary part of susceptibility is enhanced in systems with strongly interacting particles, as would be those packed in a cluster [42].…”
Section: Ac Susceptibilitymentioning
confidence: 92%
“…In addition, several other studies have reported on the effect of aggregation on AC susceptibility of magnetic nanoparticle suspensions [28,40,41], although most look at shifts in the peak of frequency response or changes in blocking temperature. However, theoretical predictions do show that imaginary part of susceptibility is enhanced in systems with strongly interacting particles, as would be those packed in a cluster [42].…”
Section: Ac Susceptibilitymentioning
confidence: 92%
“…The signatures of superparamagnetic behavior can be observed using hysteresis, where it is marked by zero coercivity and remanence and zero field cooledfield cooled (ZFC-FC) measurements where the superparamagnetic state is marked by a hump in the ZFC curve. Relaxation effects are usually studied using ac susceptibility and Mössbauer techniques [1]. Typically ac susceptibility measurements are performed in the time window of 10 À 2 -10 À 4 s and the time window for Mössbauer spectroscopy is 10 À 9 s. A systematic investigation of the blocking temperature as a function of the ac frequency helps in understanding the relaxation process and the role of interactions in the system [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid structures can be obtained by in situ polymerization of the monomer in the presence of an oxide, or by a simultaneous gelation polymerization process or formation of interfaces in the form of films (Sharma et al 2006). The sensing behaviour depends not only on the individual organic/inorganic components, but also on the nature of interface between organic and inorganic components.…”
Section: Introductionmentioning
confidence: 99%